Financial Performance and Operational Challenges of Camiguin Polytechnic State College’s Income Generating Projects - Mongaya, Jasper; Vios, Roland (JPAIR Multidisciplinary Research, 2025)
State Universities and Colleges (SUCs) in the Philippines are mandated to engage in income-generating activities to supplement institutional income and foster self-reliance. This study assesses the status of the existing Income Generating Projects (IGPs) at Camiguin Polytechnic State College (CPSC). A descriptive research design was employed, utilizing a combination of Key Informant Interviews (KIIs) and documentary analysis of secondary data from the College’s records. Data were analyzed using simple percentages and comparative analysis. The study focused on IGPs from Calendar Year (CY) 2017 to 2021 across both campuses of the College. Five IGPs were identified: Printing Services, Rental Services, Identification Card Services, Laminating Services, and Binding Services. Findings revealed a consistent decline in IGP revenue over the study period, with a sharp drop in 2020 following the temporary cessation of operations due to the COVID-19 pandemic. Contributing factors to this decline included the decentralization of certain services, such as printing, as well as delays in the arrival of supplies and materials. The operational challenges identified included limited budget allocations, inadequate production space, inefficient procurement processes, and deteriorating rental facilities. Based on these findings, the study recommends centralizing IGP operations to enhance accountability and improve reporting mechanisms, alongside addressing infrastructure and resource limitations. Such measures are crucial for strengthening the sustainability and financial performance of CPSC’s IGPs, ensuring they effectively contribute to the College’s revenue generation and operational self-reliance.